Influence of Carotino oil on in vitro rumen fermentation, metabolism and apparent biohydrogenation of fatty acids - Adeyemi, Kazeem Dauda; Ebrahimi, Mahdi; Samsudin, Anjas Asmara @ Ab Hadi; Alimon, Abdul Razak; Karim, Roselina; Karsani, Saiful Anuar; Sazili, Awis Qurni (Japanese Society of Animal Science, 2015)
The study appraised the effects of Carotino oil on in vitro rumen fermentation, gas production, metabolism and apparent biohydrogenation of oleic, linoleic and linolenic acids. Carotino oil was added to a basal diet (50% concentrate and 50% oil palm frond) at the rate of 0, 2, 4, 6 and 8% dry matter of the diet. Rumen inoculum was obtained from three fistulated Boer bucks and incubated with 200 mg of each treatment for 24 h at 39°C. Gas production, fermentation kinetics, in vitro organic matter digestibility (IVOMD), volatile fatty acids (VFA), in vitro dry matter digestibility (IVDMD), metabolizable energy and free fatty acids were determined. Carotino oil did not affect (P > 0.05) gas production, metabolizable energy, pH, IVOMD, IVDMD, methane, total and individual VFAs. However, Carotino oil decreased (P < 0.05) the biohydrogenation of linoleic and linolenic acids but enhanced (P < 0.05) the biohydrogenation of oleic acid. After 24 h incubation, the concentrations of stearic, palmitic, pentadecanoic, myristic, myristoleic and lauric acids decreased (P < 0.05) while the concentration of linolenic, linoleic, oleic and transvaccenic acids and conjugated linoleic acid (CLAc9t11) increased (P < 0.05) with increasing levels of Carotino oil. Carotino oil seems to enhance the accumulation of beneficial unsaturated fatty acids without disrupting rumen fermentation.